Utilization of GIS in the development of marine tourism in the provincial strategic tourism area (KSSP) of Carita - Aryono, Gagah Dwiki Putra; Laksana, April; Sukmawan, Irwan; Huda, Miftahul (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The development of marine tourism is crucial as it holds great potential to boost the economy, particularly in coastal areas and small islands. This is related to the potential for new income sources, economic growth, environmental awareness, cultural heritage preservation, and the promotion of infrastructure development. The purpose of this study is to design a strategy for the development of marine tourism in the Carita Strategic Tourism Area (KSPP) using GIS, in order to produce a well-structured and directed marine tourism development plan. This research uses a mixed-method approach, combining quantitative and qualitative methods, where data were collected through literature reviews, surveys, observations, and in-depth interviews with tourism stakeholders in the Carita KSPP. The research findings show that Matahari Beach has moderate attractiveness with a classification value of 660 and moderate accessibility with a classification value of 300. Karang Sari Beach has moderate attractiveness with a classification value of 540 and moderate accessibility with a classification value of 300. Meanwhile, Pasir Putih Carita Beach has high attractiveness with a classification value of 930 and high accessibility with a classification value of 300